On the Solutions and Conservation Laws of a Coupled Kadomtsev-Petviashvili Equation - Chaudry Masood Khalique (Journal of Applied Mathematics)
A coupled Kadomtsev-Petviashvili equation, which arises in various problems in many scientific applications, is studied. Exact solutions are obtained using the simplest equation method. The solutions obtained are travelling wave solutions. In addition, we also derive the conservation laws for the coupled Kadomtsev-Petviashvili equation.